2017
DOI: 10.1519/jsc.0000000000002104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polyphenol Supplementation on Acute and Chronic Response to Resistance Training

Abstract: Beyer, KS, Stout, JR, Fukuda, DH, Jajtner, AR, Townsend, JR, Church, DD, Wang, R, Riffe, JJ, Muddle, TWD, Herrlinger, KA, and Hoffman, JR. Impact of polyphenol supplementation on acute and chronic response to resistance training. J Strength Cond Res 31(11): 2945–2954, 2017—This study investigated the effect of a proprietary polyphenol blend (PPB) on acute and chronic adaptations to resistance exercise. Forty untrained men were assigned to control, PPB, or placebo. Participants in PPB or placebo groups complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 34 publications
6
27
0
2
Order By: Relevance
“…that POMj consumption inhibits Tproduction in 38 normal weight postmenopausal healthy women [78], in 23 patients with Polycystic Ovarian Syndrome [79] and among rats with Benign prostatic hyperplasia [80]. Similarly, our results are in line with recent study in healthy untrained men showing that, compared to PLA, polyphenol supplementation slightly attenuate acute plasma [T] response with no observed effect on [C] response following strength exercise [50]. The exact mechanisms explaining the post-exercise decrease in plasma [T] following POMj intake still not well established [78].…”
Section: Variables Correlationsupporting
confidence: 91%
See 4 more Smart Citations
“…that POMj consumption inhibits Tproduction in 38 normal weight postmenopausal healthy women [78], in 23 patients with Polycystic Ovarian Syndrome [79] and among rats with Benign prostatic hyperplasia [80]. Similarly, our results are in line with recent study in healthy untrained men showing that, compared to PLA, polyphenol supplementation slightly attenuate acute plasma [T] response with no observed effect on [C] response following strength exercise [50]. The exact mechanisms explaining the post-exercise decrease in plasma [T] following POMj intake still not well established [78].…”
Section: Variables Correlationsupporting
confidence: 91%
“…In order to monitor anabolic/catabolic balance during strength exercise, previous studies have investigated circulating [T] and [C] before and after strength exercises, but the existing findings are inconsistent. Indeed, while [T] increased significantly from pre to post training session in the studies of Weiss et al [67] (ΔT: 22%), Jensen et al [68] (ΔT: 27%), Crewther et al [44] (ΔT: 7%) and Ammar et al [42] (ΔT: 12%), [T] remained unchanged in other reports [50,69,70]. Surprisingly, Hakkinen et al [71] reported that, following successive strength sessions performed in 1 day, [T] may increase, decrease or not change.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations